Predicting risk along the suicidality continuum: A longitudinal, nationally representative study of the Irish population during the COVID‐19 pandemic. Issue 1 (29th June 2021) - Hyland, Philip; Rochford, Sarah; Munnelly, Anita; Dodd, Philip; Fox, Robert; Vallières, Frédérique; McBride, Orla; Shevlin, Mark; Bentall, Richard P.; Butter, Sarah; Karatzias, Thanos; Murphy, Jamie
Abstract: Introduction: Little is known about the lifetime prevalence of different indicators of suicidality in the Irish general population; whether suicidality has increased during the COVID‐19 pandemic; and what factors associated with belonging to different points on a continuum of suicidality risk. Methods: A nationally representative sample of Irish adults ( N = 1, 032) completed self‐report measures in May 2020 and a follow‐up in August 2020 ( n = 715). Results: Lifetime prevalence rates were 29.5% for suicidal ideation, 12.9% for non‐suicidal self‐injury (NSSI), and 11.2% for attempted suicide. There were no changes in past two‐week rates of NSSI and attempted suicide during the pandemic. Correlations between the indicators of suicidality supported a progression from ideation to NSSI to attempted suicide. Suicidal ideation alone was associated with being male, unemployed, higher loneliness, and lower religiosity. NSSI (with no co‐occurring attempted suicide) was associated with a history of mental health treatment. Attempted suicide was associated with ethnic minority status, lower education, lower income, PTSD, depression, and history of mental health treatment. Conclusion: Suicidal ideation, NSSI, and attempted suicide are relatively common phenomena in the general adult Irish population, and each has unique psychosocial correlates. These findings highlight important targets for prevention and intervention efforts.